Comparative impact of the affordable care act on breast cancer outcomes among women in two US states - Akinyemi, Oluwasegun; Fasokun, Mojisola; Weldeslase, Terhas; Odusanya, Eunice; Akinyemi, Irene; Geter, Kailyn; Akula, Meghana; Michael, Miriam; Hughes, Kakra; Williams, Robin (Frontiers in Oncology, 2024)
IntroductionSince the implementation of the Patient Protection and Affordable Care Act (ACA) and Medicaid expansion, states that adopted the policy have seen reduced uninsured rates. However, it is unclear whether increased healthcare access, particularly for minority and socioeconomically disadvantaged groups, has translated into measurable improvements in health outcomes.ObjectiveOur study aims to evaluate the impact of the ACA and Medicaid expansion on breast cancer outcomes in Louisiana, which has implemented the policy, compared to Georgia, which has not, as of 2024.MethodologyWe conducted a retrospective study using SEER registry data from January 2011 to December 2021, including women aged 18-64 diagnosed with breast cancer. The impact of the ACA and Medicaid expansion on cancer-specific survival (CSS), overall survival (OS), and stage at presentation was evaluated. The cohort was divided into pre-ACA (2011-2015) and post-ACA (2017-2021) periods, with a one-year washout (2016). A difference-in-difference (DID) approach compared outcomes between Louisiana and Georgia.ResultsThe study analyzed 62,381 women with breast cancer, with 32,220 cases in the pre-ACA period (51.7%) and 30,161 in the post-ACA period (48.3%). In Georgia, 43,279 women were included (52.3% pre-ACA vs. 47.7% post-ACA), while Louisiana had 19,102 women (50.1% pre-ACA vs. 49.9% post-ACA). Medicaid expansion in Louisiana was associated with a 0.26 percentage point reduction in overall deaths (95% CI: -10.9 to 10.4) and a 5.97 percentage point reduction in cancer-specific mortality (95% CI: -26.1 to 14.2). There was also no significant difference in disease stage at presentation compared to Georgia.ConclusionThis study found no significant differences in overall mortality, cancer-specific mortality, or disease stage at presentation among women with breast cancer in Louisiana, which implemented Medicaid expansion in 2016, compared to Georgia, which has not expanded Medicaid.